Persepsi Guru Terhadap Proses Pembelajaran Daring Pada Masa (Pandemi Covid-19) di SMP Negeri 1 Sawan - Suryani, Ni Nyoman Ari; Tripalupi, Lulup Endah (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the teacher's perception of the online learning process during the (covid-19) period at SMP Negeri 1 Sawan. This type of research is descriptive research with a qualitative approach to describe teachers' perceptions of the online learning process during the (covid-19) period at SMP Negeri 1 Sawan. This study uses all teachers at SMP Negeri 1 Sawan as the population and the sample used is 54 teachers. In this study, the data collection method used a questionnaire and the data analysis technique used in this study was descriptive analysis. The results showed that the teacher's perception of the cognitive aspect obtained a score of 1,665 so that it was in the good category. The teacher's perception of the affective aspect obtained a score of 1,669 so that it was in the good category. The teacher's perception of the conative aspect obtained a score of 1.764 and was in the good category. So it can be concluded that the teacher's perception of the online learning process during the (covid-19) period at SMP Negeri 1 Sawan are in good category